Comparative study of oxidized cellulose nanofibrils properties from diverse sources via TEMPO-mediated oxidation - Agus Wedi Pratama; Bambang Piluharto; Melbi Mahardika; Nurul Widiastuti; Afrinal Firmanda; Mohd Nor Faiz Norrrahim (Case Studies in Chemical and Environmental Engineering, 2024)
Cellulose nanofibrils (CNF) are promising renewable materials due to their high surface area, abundance, and ease of modification. This study explores the impact of source material on CNF properties for diverse applications like drug delivery and composites. CNF were prepared from corn cob (CC), bagasse (BG), waste wood (WW), and bacterial cellulose (BC) using TEMPO-mediated oxidation. Microcrystalline cellulose (MCC) was also oxidized (MCC-ox) for comparison. The transparency, chemical structure, crystallinity index, and surface charge of the resulting CNF were investigated. As a result, all CNF yields ranged from 25 % to 34 %. FT-IR analysis confirmed successful TEMPO oxidation by detecting carboxyl groups on all CNF surfaces. BC-derived CNF displayed the second-highest transparency after MCC. Surface charge analysis revealed the highest carboxyl content in MCC-ox (8828.39 mmol/kg), followed by CNF-BC (8438.84 mmol/kg), CNF-CC (7687.24 mmol/kg), CNF-WW (6720.43 mmol/kg), and CNF-BG (5505.61 mmol/kg). XRD analysis indicated the highest crystallinity index in MCC-ox (83.40 %) due to its high purity, followed by CNF-BC (82.52 %) likely due to its nanostructure and high purity, and CNF-CC (78.14 %) potentially due to the rigid and dense structure of corn cobs. These findings provide valuable insights into selecting CNF with the desired characteristics for various fields such as material science, nanotechnology, and biomedicine.